2013
DOI: 10.4236/ajps.2013.44104
|View full text |Cite
|
Sign up to set email alerts
|

<i>Flash microbiocide</i>: A Rapid and Economic Method for Determination of MBC and MFC

Abstract: Although nowadays there are methods for determining the Minimal Bactericidal Concentration and Minimal Fungicidal Concentration, it is indispensable that the establishment of innovative methodologies could be more practical and cheaper. The new methodology Flash microbiocide is an assay in which one aliquot from 96 well plate of Minimal Inhibitory Concentration test is transferred to another plate containing different culture medium. The correspondence with the reference methods described in the National Commi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 6 publications
1
16
0
Order By: Relevance
“…The high activity of the MICs and MBCs of macroalgae extracts against bacteria and fungi which were identified in the present study, are consistent with the results of MICs and MBCs / MFCs that were previously reported in other studies (Lambert et al, 2001;Stirk et al, 2007;El-Baky et al, 2009;Ertürk and Taş, 2011;Salem et al, 2011;Hernandes et al, 2013;Venugopa et al, 2014;Al-Judaibi et al, 2014;Zahrani et al, 2014;Veeramohan et al, 2017;Srikong et al, 2017;Martins et al 2018;Erdogan Eliuz et al, 2019;El-Sheekh et al,2020). Pesando (1990) reported that all types of antimicrobial metabolites including (green, brown red algae) exist in temperate or tropical marine.…”
Section: Resultssupporting
confidence: 92%
“…The high activity of the MICs and MBCs of macroalgae extracts against bacteria and fungi which were identified in the present study, are consistent with the results of MICs and MBCs / MFCs that were previously reported in other studies (Lambert et al, 2001;Stirk et al, 2007;El-Baky et al, 2009;Ertürk and Taş, 2011;Salem et al, 2011;Hernandes et al, 2013;Venugopa et al, 2014;Al-Judaibi et al, 2014;Zahrani et al, 2014;Veeramohan et al, 2017;Srikong et al, 2017;Martins et al 2018;Erdogan Eliuz et al, 2019;El-Sheekh et al,2020). Pesando (1990) reported that all types of antimicrobial metabolites including (green, brown red algae) exist in temperate or tropical marine.…”
Section: Resultssupporting
confidence: 92%
“…On completion of the incubation, columns with no color change were scored as above the MIC value and the fluorescence was measured using an excitation wavelength of 560 nm and emission wavelength of 590 nm. Minimum bactericidal concentrations (MBCs) were determined using the flash microbicide method, previously described [ 36 ]. The MBC is defined as the minimum concentration required to kill a certain bacterial concentration.…”
Section: Methodsmentioning
confidence: 99%
“…Minimum bactericidal concentration (MBC) was determined using previously described broth microdilution method with some modifications [ 44 ]. Briefly, 20 μL of each well after 24-h incubation were mixed with 180 μL of tryptic soy broth in a new 96-well plate and incubated statically at 37 °C and 5% CO 2 for 24 h. After incubation, 100 μL of each well were mixed with 100 μL of tryptic soy broth with 20% alamarBlue, added to a new 96-well flat-bottom plate and incubated at 37 °C and 90 rpm for 30 min.…”
Section: Methodsmentioning
confidence: 99%